2022
DOI: 10.1002/advs.202200543
|View full text |Cite
|
Sign up to set email alerts
|

Soft, Dynamic Hydrogel Confinement Improves Kidney Organoid Lumen Morphology and Reduces Epithelial–Mesenchymal Transition in Culture

Abstract: Pluripotent stem cell-derived kidney organoids offer a promising solution to renal failure, yet current organoid protocols often lead to off-target cells and phenotypic alterations, preventing maturity. Here, various dynamic hydrogel architectures are created, conferring a controlled and biomimetic environment for organoid encapsulation. How hydrogel stiffness and stress relaxation affect renal phenotype and undesired fibrotic markers are investigated. The authors observe that stiff hydrogel encapsulation lead… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…While in this work we demonstrated some level of EMT marker expression in viscoelastic hydrogels, a recent work reported by Ruiter et al. demonstrated that stress-relaxing alginate-based hydrogels down-regulated EMT associated proteins in kidney organoids [ 37 ]. Additional studies are needed to obtain conclusive results on the effect of matrix stress-relaxation on pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 41%
“…While in this work we demonstrated some level of EMT marker expression in viscoelastic hydrogels, a recent work reported by Ruiter et al. demonstrated that stress-relaxing alginate-based hydrogels down-regulated EMT associated proteins in kidney organoids [ 37 ]. Additional studies are needed to obtain conclusive results on the effect of matrix stress-relaxation on pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 41%
“…Viscoelastic hydrogels can be used to study the influence of matrix relaxation on cell morphology ( Figure 5 B), migration and proliferation, as well as to understand the cell–cell and cell–ECM interactions ( Figure 5 A). In addition, the hydrogels similar to tissues can be used for organoid incubation ( Figure 5 C) [ 57 , 126 , 127 , 128 ].…”
Section: Dynamic Covalent Chemistry Endows Novel Properties Of Hydrogelsmentioning
confidence: 99%
“…Copyright © The Royal Society of Chemistry 2014 ( B ) Thioester exchange facilitates spreading, proliferation, and migration of hMSCs in 3D scaffolds [ 57 ]. Copyright © 2018 Elsevier Ltd. ( C ) Oxime hydrogels were used to culture kidney organoids [ 126 ].…”
Section: Figurementioning
confidence: 99%
“…Recently, Geunes et al cultured kidney organoids in thiol-ene cross-linked alginate hydrogels and showed a reduction in the onset of aberrant ECM expression and off-target cell populations ( Geuens et al, 2021 ). By engineering gel mechanics and dynamics, ECM deposition and organoid maturation could be tuned, highlighting the role of engineered matrices in stirring organoid commitment ( Ruiter et al, 2022 ).…”
Section: New Strategies In In Vitro Modeling Of Ki...mentioning
confidence: 99%